A New Epigram from Bozüyük (Lamunia) - Mehmet Oktan (Gephyra, 2010)
This article presents a stele bearing an epigram which was found in 2008 during drainage work at Bozüyük, Bilecik (see map). The stele, whose upper part is broken, is made of limestone and is now at the Machine Support section of the fire department of Bozüyük. In the upper part of the stele there is a sepulchral verse consisting of 10 lines and in the lower part a frame with a profile and some figures are carved in the niches also with a profile. On the niche there is a relief which probably represents the head of the Gorgon. Within the niche there are two sections, in the upper, a lion that looks to the right, in the lower at the front, a horseman, in the back, a bull and a man. From the verse it is understood that this stele belonged to a man who died at the age of 24. The epigram was written in hexametric verse. The first line cannot be fully read because of damage to the stone. The inscription dates from the third century A.D.